Lacan for beginners - Hill, Philip (For beginners documentary comic book., 2002)
"Jacques Lacan is probably the most influential psychoanalyst since Freud (of the roughly 20,000 psychoanalysts in the world, about half are 'Lacanians') yet most people know nothing about him. The 10,000 analysts who use Lacan's ideas work mostly in France, Spain, Italy, and South America. To the rest of the world, including England and America, Lacan is a genius-in-waiting, due to be 'discovered' any day now. Despite or because of his brilliance, Lacan is difficult to understand. He wrote with an obscure, style that casually refers to philosophy, linguistics, biology, mathematics, etc.--and to make matters worse, his ideas changed over the years. Lacan For Beginners by Philip Hill introduces the reader to Lacan's theories and their relation to clinical practice in twelve elegantly structured chapters, designed around tantalizing questions that clarify Lacan's ideas. Lacan For Beginners is written with insight and wit and illustrated with examples from popular culture and cinema. The artwork is humorous and informative, and works with the text. So don't you think it is about time you become familiar with his work?" --Publisher description.